Relationship between Healthcare Provider’s Perception about Patient Safety and Patient Safety Implementation in The Emergency Department - Yayan Mulyana; Yanny Trisyani; Etika Emaliyawati (Jurnal Keperawatan Padjadjaran, 2020)
The Emergency Department (ED) is a hospital service unit that provides the first service for patients with disease conditions that threaten their lives or can cause disability for 24 hours. Implementation of patient safety in the ED should be applied to minimize the risk of error handling for the patient. ED staff perceptions related to the implementation of patient safety is a factor that directly-related to his behavior in applying the implementation of patient safety. This study aimed to analyze the relationship between perceptions of staff ED and patient safety by implementing patient safety at the Regional Hospital Emergency Department Cirebon. This study was a correlational study with the cross-sectional approach of 99 emergency staff with total sampling at Cirebon. Collecting data used questionnaires of patient safety. Based on the results of the univariate analysis showed that the majority (80%) of respondents either category on the implementation of the sub-variables of patient safety team collaboration and communication, only a small proportion of respondents less category (20%) on the implementation of the sub-variables of patient safety team collaboration and communication. In addition, less than half (49.5%) category lacking in implementing patient safety, only half (50.5%) categories, both in the implementation of patient safety. Based on the results of the bivariate analysis showed that the relationship implementation of patient safety with all the variables, namely teamwork (p-value = 0.000), communications (p-value = 0.005), the concept of patient safety (p-value = 0.005), and perception (p-value = 0.005). Based on the results of the study, the researchers concluded that the relationship between staff perceptions of the emergency department (ED) on patient safety by implementing patient safety at the Regional Hospital emergency department (RSD) Cirebon. IGD support staff perceptions of patient safety, but still found lacking in the category of health workers implementation of patient safety, so the need for patient safety education and training with simulation methods to illustrate the approach in the implementation of patient safety.